Lifestyle of university students using harmful substances and association with daily physical activity (Research, Society and Development, 2021)
The aim of this study was to analyze the lifestyle (LS) of university students who use hazardous substances and associate it with daily physical activity. For this, 1405 university students from the State University of Paraná campus of Paranavaí in Paraná were investigated in which 330 (23.4%) were identified as tobacco and/or drug users (TD) and 401 (28.5%) of alcohol (AL). In addition, about 85% of university students did not have healthy physical activity (PA) habits. The LS was measured using the “Fantastic Lifestyle” questionnaire. Thus, it was observed that the LS of university students using harmful substances, on average, was considered inadequate (TD=58.7±10.9; AL=59.6±11.0, adequate when LS≥70pts) regardless of sex. When PA was adequate (in 14.4% of cases), 9.6% were users of TD and 20% of AL, whereas, when PA was inadequate, the levels of users practically did not change in percentage (TD=10.5 % and AL=20.4%). Thus, it is concluded that the LS of university students is not suitable for health and risk reduction. There was no interference from regular and adequate physical activity in relation to the use of hazardous substances.